Numerical investigation of nanofluid flow with gold and silver nanoparticles injected inside a stenotic artery. (November 2022) - Waqas, Hassan; Farooq, Umar; Liu, Dong; Alghamdi, Metib; Noreen, Sobia; Muhammad, Taseer
Graphical abstract: Highlights: Flow problem is modeled as a cylindrical surface with stretching and shrinking phenomenon. Gold and silver nanoparticles with human blood characteristics are scrutinized through the stenotic artery. Magnetohydrodynamics and thermal radiation aspects are considered. The bvp4c scheme is utilized via computational software MATLAB. Abstract: The main aim of the current framework is to scrutinize the importance of gold and silver nanoparticles submerge in the human blood in the presence of magnetohydrodynamics (MHD) flow inside a stenotic artery. The primary reason for adopting gold and silver nanoparticles as nanomaterials for drug delivery is because they exhibit potential drug transport and imaging properties. The temperature and the velocity of the blood gradually decline as increment the size of the nano particles of gold. Furthermore, the effects of heat source-sink and thermal radiation are considered. To convert the partial differential equations (PDEs) into dimensionless ordinary differential equations (ODEs), a method of suitable similarity transformations has been utilized and then solved by using the bvp4c built in solver in MATLAB mathematical software to get the numerical solutions as well as the graphical results. Higher order ordinary differential equations (ODEs) are than tackled via shooting scheme. The outcomes of physical controlling parameters via temperature and velocity profiles are elaborated through graphs. The thermal distribution profile shows increasing behavior for the raising variations of Biot number and thermal radiation parameter. The current approach has the potential to be highly beneficial for efficient drug delivery in blood.